2020
DOI: 10.22190/fume190509032m
|View full text |Cite
|
Sign up to set email alerts
|

CFD Modelling of Formula Student Car Intake System

Abstract: Formula Student Car (FS) is an international race car design competition for students at universities of applied sciences and technical universities. The winning team is not the one that produces the fastest racing car, but the group that achieves the highest overall score in design, racing performance. The arrangement of internal components for example, predicting aerodynamics of the air intake system is crucial to optimizing car performance as speed changes. The air intake system consists of an inlet nozzle,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Over the last decades, the automotive industry has been increasingly incorporating new engine technologies [1], with major innovations in the Electrical/Electronic (E/E) systems [2]. Due to the complexity of new developments, the most important parameters, such as highest power, lowest emissions, and best fuel economy, heavily depend on the AFR values, an example being shown in Figure 1 [3].…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decades, the automotive industry has been increasingly incorporating new engine technologies [1], with major innovations in the Electrical/Electronic (E/E) systems [2]. Due to the complexity of new developments, the most important parameters, such as highest power, lowest emissions, and best fuel economy, heavily depend on the AFR values, an example being shown in Figure 1 [3].…”
Section: Introductionmentioning
confidence: 99%
“…A CFD modeling of formula student car of intake system was performed by Mohamad et al [19], which showed better simulation quality compared to the previous models. In order to save a substantial amount of time and resources, using the AVL-Boost software, the intake system was examined acoustically and simulated by means of 1-D gas dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…The new optimization technique for mixture formation in direct injection into the gasoline engine was summarized by Chincholkar and Suryawanshi [18]. In order to build and optimize the intake system by eliminating secondary injectors, Mohamad et al [19] used coupled method technique and applied new location for the primary injectors for the Formula race car engine, power output, torque, specific fuel consumption, along with three-dimensional air flow to the engine were monitored. Mohamad et al [20] used CFD tools to conduct different design phases to test two major flow properties that are intake system velocity and pressure.…”
mentioning
confidence: 99%